What Counts is not Falling … but Landing(): Strategic Analysis: An Adapted Model for Implementation Evaluation - BROUSSELLE, ASTRID (2004)
Implementation evaluations, also called process evaluations, involve studying the development of programmes, and identifying and understanding their strengths and weaknesses. Undertaking an implementation evaluation offers insights into evaluation objectives, but does not help the researcher develop a research strategy. During the implementation analysis of the UNAIDS drug access initiative in Chile, the strategic analysis model developed by Crozier and Friedberg was used. However, a major incompatibility was noted between the procedure put forward by Crozier and Friedberg and the specific characteristics of the programme being evaluated. In this article, an adapted strategic analysis model for programme evaluation is proposed.